Performance analysis of multi-user detection of 5G overloaded sporadic system - Guoyu MA; Bo AI; Xian’an HU; Xiaobing JIANG (Dianxin kexue)
Currently，MTC has two main characteristics：massive connectivity and sporadic transmission.Massive connectivity makes the access behavior non-orthogonal and the sporadic characteristic makes the user activity sparsity.Based on those characteristics，some literatures introduce a corresponding detection technique called compressive sensing based multi-user detection.Performance of multi-user detection technique was analyzed by evaluating the user activity detection performance and the user data detection performance.The simulation results conclude that the detection performance will be influenced by the cross correlation between the non-orthogonal spreading sequences，but CS-MUD can still support the massive connection scenario in which the user activity is sparse.